2020
DOI: 10.1111/bjet.13006
|View full text |Cite
|
Sign up to set email alerts
|

Humanoid robots in higher education: Evaluating the acceptance of Pepper in the context of an academic writing course using the UTAUT

Abstract: This study investigates the acceptance of social robots by higher education students in the social sciences. Pepper, a humanoid social robot from SoftBank Robotics, provided a sample of its capabilities during a first semester, large‐scale, university course, “Introduction to academic writing.”From this course, 462 freshmen participated in our survey. The unified theory of acceptance and use of technology (UTAUT) acts as the conceptual framework, and partial least squares structural equation modelling (PLS‐SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 53 publications
1
42
2
Order By: Relevance
“…Humanoid robots can make users feel their physical and social presence [ 13 , 43 ]. The robot used in this study has a human-shaped structure and is capable of simple dialogue and physical interaction with the user.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humanoid robots can make users feel their physical and social presence [ 13 , 43 ]. The robot used in this study has a human-shaped structure and is capable of simple dialogue and physical interaction with the user.…”
Section: Discussionmentioning
confidence: 99%
“…Robots can serve as peers or mentors of learners and can effectively improve learners’ cognition and affection [ 12 ]. In addition, it is worth noting that traditional learning technology lacks the robot’s characteristic of physical presence [ 13 ]. The functions and interaction methods of robots are different from those of computers, tablets, and mobile phones.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical model highlights performance expectancy, effort expectancy, social influence, and facilitating conditions as essential predictors of technology acceptance and use. Thus far, the extant literature shows that performance expectancy, effort expectancy, and social influence significantly affect behavioural intention to use AI [34]. Nevertheless, no study was found that tested the effect of facilitating conditions on AI adoption.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Theoretically, this antecedent has been explained using theories like 1 Frequency in parentheses. service robot acceptance model [39], and by extending established theories like UTAUT [18], [32], [34], TAM [9], [46], [48], and parasocial relationship theory [40], [41]. Furthermore, anthropomorphism is the only antecedent of AI adoption that classic technology adoption theories do not explain.…”
Section: Antecedents Of Ai Adoptionmentioning
confidence: 99%
See 1 more Smart Citation